A solid-to-solid metallic conversion electrochemistry toward 91% zinc utilization for sustainable aqueous batteries - Hou, Zhiguo (2022)
The diffusion-limited aggregation (DLA) of metal ion (Mn+) during the repeated solid-to-liquid (StoL) plating and liquid-to-solid (LtoS) stripping processes intensifies fatal dendrite growth of the metallic anodes. Here, we report a new solid-to-solid (StoS) conversion electrochemistry to inhibit dendrites and improve the utilization ratio of metals. In this StoS strategy, reversible conversion reactions between sparingly soluble carbonates (Zn or Cu) and their corresponding metals have been identified at the electrode/electrolyte interface. Molecular dynamics simulations confirm the superiority of the StoS process with accelerated anion transport, which eliminates the DLA and dendrites in the conventional LtoS/StoL processes. As proof of concept, 2ZnCO3·3Zn(OH)2 exhibits a high zinc utilization of ca. 95.7% in the asymmetry cell and 91.3% in a 2ZnCO3·3Zn(OH)2 || Ni-based full cell with 80% capacity retention over 2000 cycles. Furthermore, the designed 1-Ah pouch cell device can operate stably with 500 cycles, delivering a satisfactory total energy density of 135 Wh kg-1.